1993
DOI: 10.1111/j.1365-3024.1993.tb00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Epitope specificity and capacity to inhibit parasite growth in vitro of human antibodies to repeat sequences of the Plasmodium falciparum antigen Ag332

Abstract: It has earlier been shown that the Plasmodium falciparum-reactive human monoclonal antibody 33G2 inhibits parasite growth in vitro as well as cytoadherence of infected red blood cells to melanoma cells in vitro. MoAb 33G2 recognizes an epitope of the P. falciparum antigen Ag332 and cross-reactive determinants in Pf155/RESA and Pf11.1 located in repetitive regions containing sequences of regularly spaced pairs of glutamic acid. To study whether antibodies of this specificity frequently occur in human immune ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…9 Moreover, analysis of the epitope specificity of human Pf332-reactive antibodies suggested that a multitude of Pf332 repeats constitute B cell epitopes. 10 The importance of Pf332-reactive antibodies for protective immunity against P. falciparum asexual blood stages is indicated by several findings. Antibodies to Pf332 repeats, raised in animals or affinity purified from human serum, inhibit in vitro parasite growth.…”
mentioning
confidence: 99%
“…9 Moreover, analysis of the epitope specificity of human Pf332-reactive antibodies suggested that a multitude of Pf332 repeats constitute B cell epitopes. 10 The importance of Pf332-reactive antibodies for protective immunity against P. falciparum asexual blood stages is indicated by several findings. Antibodies to Pf332 repeats, raised in animals or affinity purified from human serum, inhibit in vitro parasite growth.…”
mentioning
confidence: 99%
“…4,5 This approach has led to the identification of several vaccine candidate antigens from the blood stage of P. falciparum. [6][7][8] Involvement of antibodies in immune protection against P. falciparum blood stages has been established by passive antibody transfer studies in humans. In these studies, several investigators have found that passive transfer of IgGs from immune adults to nonimmune infected children causes a marked decrease in P. falciparum parasitemias 1,[9][10][11][12] Investigations from the laboratory of Druilhe identified the cooperation of antibodies with monocytes in protection against malaria.…”
mentioning
confidence: 99%
“…The Pf332-derived epitope, VTEEI, is recognized by the parasite neutralizing human mAb 33G2. 18,20,25 Moreover, human antibodies, affinity purified from malaria immune sera on synthetic peptides comprising this Pf332 epitope, also have the capacity to inhibit parasite growth in vitro, 16,17 as have rabbit antibodies induced by MAP1 and MAP2. 26 When H-2 congenic mice were injected with MAP1, high antibody levels were induced in H-2 d mice, whereas the responses in H-2 q and H-2 k (and other I-A k -expressing mice) were lower.…”
Section: Discussionmentioning
confidence: 99%
“…12,14,15 Pf332-reactive antibodies have been reported to inhibit parasite growth in vitro. 16,17 Furthermore, the growth inhibitory Pf332-reactive human monoclonal antibody (mAb) 33G2 also inhibits cytoadherence of PRBC to endothelial cells in vitro. 18,19 The motif VTEEI and structurally related sequences occurring multitudinously in Pf332 constitute epitopes for mAb 33G2, as well as for growth inhibitory Pf332-reactive antibodies isolated from human malaria immune sera.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation